Factors influencing in-vitro embryo production efficiency of caprine oocytes: A review - KHARCHE, S D; GOEL, PUJA; JHA, BIPUL KUMAR; GOEL, A K; JINDAL, S K (The Indian Journal of Animal Sciences, 2011)
Pre-implanted growth and development of embryo is deficient in many aspects as is evidenced by the great difficulty in growing embryos in-vitro, while maintaining viability as shown by development of early embryos in-vitro generally delayed or completely blocked at 8–16 cell stage embryo and hardly small percentage of the in-vitro fertilized embryo develop to morula and blastocyst, which is probably due to minor physio- chemical variation and lack of certain factors in the culture system. In-vitro development of mammalian embryos usually remains inferior to development than invivo produced embryos. The mechanism regulating the in-vitro acquisition of developmental competence of oocytes is still obscure. Therefore it is needed to standardize the culture conditions that mimic in-vivo embryo development. To know the exact mechanism of developing embryos, there should be a defined system that caters the needs of developing embryos. The current review describes the criteria and factors affecting in-vitro maturation, fertilization and embryo development in goa